Individual Differences and MIS Success: A Review of the Empirical Literature - Zmud, Robert W. (Management Science, 1979)
Of the numerous factors believed to influence MIS success, the area of individual differences has by far been the most extensively studied. This paper synthesizes the findings of empirical investigations of the manner in which individual differences impact MIS success. Suggestions are made regarding those aspects which would benefit most from future research.